150k views
2 votes
Solve: −3(k − 2) = −2

2 Answers

4 votes

Answer:8/3

Step-by-step explanation:divide both sides by -3 2 negative make a positive add 2 to both sides simplify 2/3 +2 to 8/3

User Martinaut
by
4.7k points
5 votes

Answer:

The answer is


\huge \boxed{k = (8)/(3) } \\

Explanation:


−3(k − 2) = −2

Expand the terms in the bracket

That's


- 3k + 6 = - 2

Subtract 6 from both sides of the equation

We have


- 3k + 6 - 6 = - 2 - 6 \\ - 3k = - 8

Divide both sides by - 3


( - 3k)/( - 3) = ( - 8)/( - 3) \\

We have the final answer as


k = (8)/(3) \\

Hope this helps you

User Malte Schwerhoff
by
5.0k points